A possible early reference to the Gypsies in Spain prior to 1420 Ms. 940 of the Trivulziana Library in Milan, Italy. Issue 1 (June 2016) - TAYLOR, AARON C.
Abstract : Manuscript 940 of the Trivulziana Library – also known as the Cancionero de la Trivulziana – contains a little-known apocalyptic text written originally in 1420: Las señales que serán quando el Antecristo verná a reinar ('The signs that shall be when the Antichrist comes to reign'). Written by an anonymous follower of Pope Benedict XIII (r. 1394–1423), this list of forty prophecies and accompanying commentary purport to signal the coming of the Antichrist in 1430. The commentary to one of these signs notes the arrival of a nomadic group to central Spain, possibly Gypsies, a few years prior to the text's composition. The article provides a description of the manuscript and analyzes this possible reference to the Gypsies in the Iberian Peninsula.